IMPLEMENTASI ENTERPRISE RESOURCES PLANNING (ERP) PADA LEMBAGA KEUANGAN MIKRO SYARIAH - Miswan Ansori; Ahmad Fauzan Mubarok (Wahana Islamika: Jurnal Studi Keislaman, 2021)
Technological developments in the financial industry or financialtechnology require Islamic microfinance institutions to be able to adapt and usetechnological developments in order to remain competitive with other financialinstitutions. This study analyzes how the implementation of Enterprise ResourcesPlanning carried out at the Islamic microfinance institution KSPSS BMT BUS inintegrating and automating all business processes that occur at the Islamicmicrofinance institution. This research method is carried out with descriptivequalitative methods by conducting Value Chain analysis and SWOT analysis.From the research results, it can be concluded that the research results show thatthe implementation process carried out has several shortcomings, namely highcosts, the implementation process that takes a long time, a limited nominaltransaction, an open security system, and dependence on the network. However,on the other side of this process, there are also advantages, namely an integratedsystem of all branches, faster transaction processing, increased company revenueand a wider partner network.